Nebivolol Exerts Hepatoprotective Activity During CLP-Induced Sepsis by Modulating Oxidative Stress, Liver Regeneration, and AKT/MAPK Pathways in Rats - Rahma Tharwat Sabra; Amany Abdlrehim Bekhit; Nourhan Tharwat Sabra; Nadia Ahmed Abd El-Moeze; Moustafa Fathy (Stresses)
Sepsis is a potentially catastrophic organ dysfunction arising from an infection-induced immunologic reaction leading to severe inflammation, progression of septic shock, and damage to body organs. Sepsis is marked by noticeable hepatotoxicity caused by activating oxidative stress, inflammation, and apoptotic mechanisms. Through Cecal Ligation and Puncture (CLP) in rats, our study is the first to investigate the potential preventive effect of the antihypertensive medicine “Nebivolol” on sepsis-induced hepatotoxicity at a molecular level. Six groups of sixty albino Wistar rats (male) were randomly assigned. Biochemical and oxidative stress markers of liver function were measured. Additionally, apoptosis- and inflammatory-related gene and protein expressions were examined. Finally, the liver tissues were examined for histological assessments. The hepatic architecture was considerably altered by CLP, which also resulted in marked elevations of blood aspartate aminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), total and direct bilirubin levels, and hepatic malondialdehyde (MDA). In contrast, it decreased serum albumin level, hepatic superoxide dismutase (SOD) activity, and glutathione (GSH) level. It also significantly elevated all hepatic inflammatory mediators (Interlukin-6 (IL-6), Tumor Necrosis Factor-alpha (TNF-α), and Interlukin-1 beta (IL-1β)) and alleviated Interlukin-10 (IL-10). It magnified the expression of p-AKT/t-AKT, p-JNK1/2/t-JNK1/2, and p-p38/t-p38 proteins, raised Matrix Metalloproteinase 2/9 (MMP 2/9) and nuclear factor-kappa B (NF-κB) gene transcriptions, and lessened Vascular Endothelial Growth Factor (VEGF) gene expression. In contrast, Nebivolol administration dramatically mitigated all biochemical and histological changes obtained by CLP. The present finding demonstrated that Nebivolol succeeded, for the first time, in improving the hepatic injury obtained from CLP-evoked sepsis through modulating oxidative stress, inflammatory mediators, and apoptotic pathways through targeting the crosstalk between protein kinase B (AKT), NF-κB, and mitogen-activated protein kinase (MAPK), making Nebivolol a hopeful treatment for hepatic injury.